The grapes of wrath - Steinbeck, John, 1902-1968. (New York, N.Y. : Penguin Books, 1986)
A family of thirteen must leave their farm in Oklahoma to find work. They become migrant workers in California.
Young Adult
Young Adult.
Wilson's Senior High School
Wilson's Fiction
Booklist
680
Keywords: Migrant agricultural laborers -- California -- Fiction; Labor camps -- California -- Fiction; Migrant labor -- Fiction; California -- Fiction; Historical fiction